Minimizing complications following transinguinal preperitoneal modified Kugel mesh herniorrhaphy: a double blind prospective randomized clinical trial - Heng-Chieh Chiang; Jesun Lin; Jian-Ting Chen; Yu-Chi Hsu; Pao-Hwa Chen (Scientific Reports, 2022)
Abstract Transinguinal preperitoneal (TIPP) single-layer mesh herniorrhaphy has been proven effective. Mesh manufacturers make either a single-unit, two-layer mesh design or a separate optional onlay with the pre-peritoneal mesh. For peace of mind, most surgeons still incorporate the optional onlay. This study evaluated any counterproductive effects of adding the onlay to single-layer TIPP mesh herniorrhaphy and compared the long-term efficacy. This prospective, single-surgeon, single-center, randomized trial compared two groups of 50 consecutive patients at a 1 to 1 ratio. The control group received a single-layer modified Kugel mesh in the preperitoneal space, while the study group received the optional onlay mesh in the inguinal canal with preperitoneal mesh placement. A single surgeon performed the same operation to place the preperitoneal mesh in both groups, the only difference being the placement of the optional onlay mesh in the study group. A blinded researcher performed post-operative interviews using a series of questions at 1, 3, 6, and 12 months after surgery, and another unblinded researcher organized and performed statistical analysis of the peri-operative and post-operative data. The primary endpoints included foreign body sensation, pain, and any other discomfort in the inguinal region following surgery; and the secondary endpoints included recurrence and any complications related to surgery. The patient demographics were similar between the two groups. The average follow-up period was 29 months. Two patients in the 1-layer group and one patient in the 2-layer group were lost to follow-up. Postoperative pain, numbness and soreness were similar between groups. No patients experienced a foreign body sensation after 3 months in the 1-layer group, while five patients still had a foreign body sensation at 12 months in the 2-layer group. No recurrence was noted in either group during the follow-up period. Adequate dissection of the preperitoneal space is the key to a successful single-layer TIPP herniorrhaphy. With decreased materials in the inguinal canal, single-layer TIPP has a lower rate of long-term postoperative discomfort without increasing the risk of future recurrence. Trial registration: ISRCTN 47111213